Utilization bottom ash from incinerator become paving block: (Study case : PT. X) - Ismail , Yunita; Maulida, Afina (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Bottom ash incinerator produced by PT. X from various waste from production tenant activities has physical characteristics like cement, so it possible to use it as a substitute for cement in paving block mixtures. This utilization aims to determine the effect of using bottom ash on paving blocks according to the compressive strength and water absorption parameter. The composition of cement, and bottom ash in making paving block was varied in this experiment, for amount of sand and water used were same. Drying process for the paving block took 28 days. The bottom ash replace cement by 0 percent, 5 percent, 10 percent and 15 percent respectively, and two replications done for measurement. The quality of paving block was test based on the SNI 03-0619-1996 to determine the level of quality of paving block. The results of this study indicate that the treatment used were significance different based on compressive strength but were not significance different based on water absorption parameter. The substitution of bottom ash in paving blocks based on compressive strength, for treatment C (with 10 percent bottom ash) complied with quality B and treatment D (with 15 percent bottom ash) complied with quality D of paving block standard. Based on water absorption parameter all treatment complied with quality B and D (treatment A, B, and D complied with quality D and treatment C complied with B quality). By considering booth parameter, treatment C (with 10 percent bottom ash) complied with B quality and treatment D (with 15 percent bottom ash) complied with D quality. Other finding from these research showed at least 10 percent bottom ash from incinerator replaced cement used in making paving block.